A role of corporate image as a successful determinant of human resource management strategy and marketing strategy in the firm performance of hospitality industry In Indonesia - Harianto Respati; Boge Triatmanto; Mokhamad Natsir; Djoko Hanantijo (Cogent Business & Management, 2024)
Improving the performance of the national hospitality industry is crucial, considering the ongoing rise in foreign and local tourist arrivals, which are estimated to be influenced by marketing strategies and the role of hotel employees. This study aims to investigate the influence of human resource management and marketing strategies on corporate image within a competitive market context, particularly in the hospitality sector. Moreover, it explores whether corporate image mediates between human resource management strategies, marketing strategies, and firm performance. Previous research overlooked the significance of corporate image for success in this industry. Data were collected through a questionnaire survey targeting 232 hotel managers in East Java, Indonesia. Structural equation modeling analysis reveals that marketing strategy positively impacts corporate image, thereby enhancing firm performance. The conclusion of this study emphasizes the direct effect of marketing strategy on firm performance, especially through pricing strategies that consider competitor prices, resulting in increased sales growth rates. These findings suggest that setting room occupancy prices positively influences market confidence. Hence, practitioners must carefully determine room prices in the current digital communication era, where potential buyers can access data swiftly through digital communication devices. Consequently, pricing has become a sensitive aspect and an opportunity for future researchers to elucidate the appropriate pricing strategy.
Keywords: 650; HRM strategy; marketing strategy; corporate image; firm performance; hospitality industry